2014
DOI: 10.1210/jc.2014-2494
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea Treatment Before Genetic Testing in Neonatal Diabetes: Pros and Cons

Abstract: Sulfonylurea therapy appears to be safe and often successful in neonatal diabetes patients before genetic testing results are available; however, larger numbers of cases must be studied. Given the potential beneficial effect on neurodevelopmental outcome, glycemic control, and the current barriers to expeditious acquisition of genetic testing, an empiric inpatient trial of sulfonylurea can be considered. However, obtaining a genetic diagnosis remains imperative to inform long-term management and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 31 publications
1
48
0
1
Order By: Relevance
“…It is also apparent from several studies that glycemic control is dissatisfactory in NDM patients on insulin momotherapy (14). Furthermore, early SU treatment can improve glycemic control and ameliorate neurodevelopmental disability among neonatal patients with KCNJ11 mutations that are commonly found in patients with NDM (14)(15)(16)(17). With these pieces of evidence, the high efficiency of SU therapy shown in our study suggested that SU can be considered as a first-line treatment for patients with NDM.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…It is also apparent from several studies that glycemic control is dissatisfactory in NDM patients on insulin momotherapy (14). Furthermore, early SU treatment can improve glycemic control and ameliorate neurodevelopmental disability among neonatal patients with KCNJ11 mutations that are commonly found in patients with NDM (14)(15)(16)(17). With these pieces of evidence, the high efficiency of SU therapy shown in our study suggested that SU can be considered as a first-line treatment for patients with NDM.…”
Section: Discussionsupporting
confidence: 55%
“…It was generally recommended that SU treatment should be initiated for a patient with NDM once his/her genetics were confirmed to be associated with the overactivation of the K ATP channel (22) despite it being challenged by the inefficiency of genetic diagnosis that may deprive the neonates of benefits gained by the early introduction of SU (15)(16)(17)23). In our study the success of SU monotherapy in 94% (15/16) patients with NDM without noticeable side effects suggested that SU can be an efficient treatment in NDM patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The underlying genetic cause remains unknown in 20–30% of neonatal diabetes cases,6 7 and the University of Chicago Monogenic Diabetes Registry was established to identify novel aetiological genetic mechanisms in families with suspected monogenic diabetes, in addition to following families with known forms of monogenic diabetes. Here we outline the identification of a deep intronic INS mutation causing diabetes through a novel mechanism.…”
Section: Introductionmentioning
confidence: 99%